Automated aquaponic water quality management system - Zakaria, Muhammad Hazim; Abu Bakar, Zahari; Mohd. Atan, Fadila; Mokhtar, Siti Musliha Ajmal (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
This technical report presents the design and simulation of an Automated Aquaponic Water Quality Management System (AAWQMS) to ensure water quality for plants and fish using Arduino-based sensors and actuators. The system integrates an ultrasonic sensor for water level, a DS18B20 temperature sensor, and a simulated pH sensor, with real-time data visualization provided by a Liquid Crystal Display (LCD). Enhanced by an ESP8266 Wi-Fi module, the system is transformed into an Internet of Things (IoT) device, enabling remote monitoring and control. Using the Proteus simulation platform, the Arduino microcontroller processes data from the sensors to monitor and regulate critical aquaponic parameters. Additional components, including a servo motor for fish feeding, a relay module to control the water pump, and an alert system via Blynk, expand the system’s functionality. The Arduino code features intelligent decision-making, dynamically controlling the relay module, servo motor, and Blynk alerts based on predefined thresholds for temperature, pH, and water level. The LCD provides real-time feedback, displaying temperature and pH values, while the Blynk app allows users to monitor these parameters and water level on their mobile devices. The AAWQMS offers a scalable and efficient solution for automated aquaponic management, combining IoT connectivity for enhanced accessibility and control